Priorities in teacher education the 7 key elements of pre-service preparation - Kosnik, Clare Madott. (Routledge, 2009)
Advocating concentrating on certain priorities to ensure beginning teachers are prepared for the crucial tasks that will face them, this book discusses seven prioritiesẗhrough case studies.